Exploiting a low tax system: non-tax-induced cigarette price increases in Taiwan 2011–2016 - Gao, Wayne; Sanna, Mattia; Branston, J Robert; Chiou, Hung-Yi; Chen, Yi-Hua; Wu, Allison; Wen, Chi Pang (Tobacco control, 2019)
IntroductionThis study aims to analyse the non-tax-induced price increasing strategies adopted by tobacco industry in Taiwan, a high-income country with comprehensive tobacco control policies but low tobacco taxes and a declining cigarette market.MethodsUsing governmental tax, price and inflation data, we analysed cigarette sales volume, affordability, affordability elasticity of demand, market share, pricing and net revenue of the top five tobacco companies in Taiwan from 2011 to 2016 when no tax increases occurred.ResultsTotal revenue after tax grew significantly for all the major transnational tobacco companies between 2011 and 2016 at the expense of the state-owned Taiwan Tobacco and Liquor Corporation. In terms of market share, Japan Tobacco (JT) was the leading company, despite experiencing a small decline, while British American Tobacco and Imperial Brands remained stable, and Philip Morris International increased from 4.7% to 7.0%. JT adopted the most effective pricing strategy by increasing the real price of its two most popular brands (Mevius and Mi-Ne) and, at the same time, doubling the sales of its cheaper and less popular brand Winston by leaving its nominal retail price unaltered.ConclusionsLow and unchanged tobacco taxes enable tobacco companies to use aggressive pricing and segmentation strategies to increase the real price of cigarettes without making them less affordable while simultaneously maintaining customers’ loyalty. It is crucial to continue monitoring the industry’s pricing strategies and to regularly increase taxes to promote public health and to prevent tobacco industry from profiting at the expense of government revenues.